A6_4 Take Us Up - Gorringe, Peter; Pizarro Salcedo, Claudio; Price, Tom; Bristowe, Thomas (Physics Special Topics, 2021)
The Federation Starfleet Starship U.S.S. Voyager, the titular vessel in the 1995-2001 TV Show Star Trek: Voyager, was the first televised vessel in the Star Trek universe to feature landing gear. In this paper, we will analyse the required thrust to launch U.S.S. Voyager into an orbit of 250 km above Earth, the same orbit of the International Space Station. We further find that the required thrust in this scenario is comparable to that of ∼ 2640 Saturn V Rockets. This means the cost of launching Voyager today is ∼ $1.4 Trillion.